Solution Of Scaler Riemann Hilbert Problems - Dr. Abdel Radi Abdel Rahman Abdel Gadir Abdel Rahman; Amna Eltahir Mokhtar Eltahir (IJRDO -JOURNAL OF MATHEMATICS, 2024)
in this paper we give a mathematical formulation of the Riemann Hilbert problem. We then proceed to show scaler and the solution of scaler of Riemann-Hilbert problem arises in the theory to this. To do this we formula and solve some problems and solution. the Solution of Scaler Riemann Hilbert problem depend to Holder Condition, pemelj formula, and Hardy spaces